The Rapid and Long-Lasting Antidepressant Effects of Iridoid Fraction in Gardenia Jasminoides J.Ellis Are Dependent on Activating PKA-CREB Signaling Pathway - Ren, Li; Zhang, Hailou; Tao, Weiwei; Chen, Yin; Zou, Zhilu; Guo, XiaoYan; Shen, Qinqin; Feng, Quansheng; Hu, Jingqing (Frontiers in Pharmacology, 2022)
Lag periods of therapeutic efficacy causes poor compliance of patients. This has made rapid antidepressant the most urgent problem needed to be solved in depression study field at present. Our previous studies identified rapid antidepressant effects of traditional herb Gardenia jasminoides Ellis (GJ) and its standardized fractions. Through screening for different fractions of GJ, we focused on iridoids fraction of GJ (GJ-IF). Methods: 1. Tail suspension test (TST), Forced swimming test (FST) and Novelty suppressed-feeding test (NSFT) were performed in sequence on mice after GJ-IF administration. 2. Mice in model group were under Chronic Unpredictable Mild Stress (CUMS) for 3 w. After GJ-IF treatment, mice were placed in Open field test (OFT), Sucrose preference test (SPT), NSFT, TST and FST. 3. Western Blot was performed to examine the expression of Brain-derived neurotrophic factor (BDNF), Synapsin1, cyclic-AMP dependent protein kinase A (PKA), Phosphorylated cyclic-AMP responsive element binding protein (p-CREB) and cAMP response element-binding protein (CREB). 4. Mice in the test group were administrated with GJ-IF after intraperitoneal injection of PKA blocker H89. Results: 1. GJ-IF treatment significantly reduced the immobility time of TST at 1 d and FST at 26 h. 2. GJ-IF reversed the deficits induced by 3 w CUMS in SPT, TST, FST and NSFT at 1 d, 26 h. The antidepressant effects of a single dose of iridoids fraction could also last for at least 14 d; 3. The results of molecule studies suggested a single dose of GJ-IF activated p-CREB at 2h and PKA-CREB pathway at 1 d. The expression of BDNF didn’t have significant change from 30 min to 1 d after GJ-IF administration. 4. Blockade of PKA-CREB signaling pathway reversed the antidepressant effects of GJ-IF at 1 d, but not 30 min and 2 h. Conclusion: GJ-IF is the key component in rapid antidepressant of GJ. Rapid and sustained antidepressant effects of GJ-IF were dependent on activating of PKA-CREB signaling pathway.